2009
DOI: 10.1158/1055-9965.epi-09-0620
|View full text |Cite
|
Sign up to set email alerts
|

Chinese “Herbal” Cigarettes Are as Carcinogenic and Addictive as Regular Cigarettes

Abstract: Objective: To examine the Chinese tobacco industry's claim that herbal cigarettes are less harmful than regular cigarettes. Methods: The study design was a cross-sectional survey. One hundred thirty-five herbal cigarette smokers and 143 regular smokers from one city in China completed a questionnaire on smoking behavior and provided a urine sample. The main outcome measures were cotinine and trans-3′-hydroxycotinine in all samples, and polycyclic aromatic hydrocarbon metabolites (PAH; 1-hydroxypyrene, naphthol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 8 publications
(10 reference statements)
0
23
0
Order By: Relevance
“…The tobacco industry also promotes products with fruity flavor, such as the “DJ Mix Light” with strawberry flavor. Some products feature “herbs” and “ginseng” as ingredients and are mislabeled as health promoting [46]. In summary, cigarette companies are trying to support a “new normal” for smoking among women—not only acceptable but also desirable, liberating, fashionable, and “glorious”.…”
Section: Discussionmentioning
confidence: 99%
“…The tobacco industry also promotes products with fruity flavor, such as the “DJ Mix Light” with strawberry flavor. Some products feature “herbs” and “ginseng” as ingredients and are mislabeled as health promoting [46]. In summary, cigarette companies are trying to support a “new normal” for smoking among women—not only acceptable but also desirable, liberating, fashionable, and “glorious”.…”
Section: Discussionmentioning
confidence: 99%
“…The tobacco industry also used prominent academic figures as spokespersons for the industry and to justify the ‘less harmful, low-tar’ strategy 47. In contrast, independent research showed that low-tar and herbal cigarettes in China do not deliver lower doses of nicotine or carcinogens 48 49…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence, while limited, suggests that the Chinese tobacco industry behaviour in some areas is similar to what the transnational tobacco companies have been doing in the west, from the promotion of cigarettes using popular athletes53 to unjustified claims that low-tar and herbal cigarettes were less harmful products 48 49. In September 2009, a Chinese tobacco industry official openly questioned the science behind passive smoking during a public hearing on smoke-free legislation in Shanghai 54…”
Section: Discussionmentioning
confidence: 99%
“…Gan et al . [63] claimed that Chinese “Herbal” Cigarettes are as carcinogenic and addictive as regular cigarettes. Concerning e-cigarettes, McCauley et al .…”
Section: Cigarette Toxicity and Vulnerable Population Groupsmentioning
confidence: 99%